Aspek Agama, Sosial dan Budaya dalam Kurikulum Pendidikan dan Pembelajaran Seni Budaya Keagamaan Hindu yang Berkearifan Lokal - I Wayan Agus Gunada; I Wayan Lasmawan; I Gusti Putu Suharta (Cetta: Jurnal Ilmu Pendidikan, 2023)
The purpose of writing the results of this study is to explain the importance of religious and socio-cultural factors in the development of the Hindu religious art and culture education curriculum. Learning art and culture, especially in the Hindu education curriculum, is not only to teach aspects of art but, most importantly, to internalize Hindu values in Hindu art. Thus, religious adaptation strengthens the value of spirituality, and socio-cultural aspects are for material improvement in strengthening art and culture with local wisdom. This study uses a qualitative approach of the type of literature study, with a data collection method, namely literature analysis, that is relevant to the focus of the study. Analysis techniques use continuous models, namely reduction, presentation and verification of data. Based on the results of data analysis, religious factors are essential in providing reinforcements of Hindu values, especially the concept of art in Hinduism, so that art material is related to the ability to be creative and aspects of spirituality. Social and cultural aspects reinforce the development of the art education curriculum, so the existing art aspects focus more on regional art and culture development. Thus, this study can explain the importance of religious, social and cultural aspects adopted in developing the Hindu religious art and culture education curriculum. Moreover, it can use as a reference in relevant studies in the future.